DFT study of the amine diazotization reaction - Poleshchuk O. Kh. Oleg Khemovich; Fedorova V. A. Valentina Antonovna; Yarkova A. G. Anna Gennadjevna; Filimonov V. D. Viktor Dmitrievich (2015, 2015)
Title screen